2020
DOI: 10.21203/rs.3.rs-35501/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Periodic Curcumin Monoglucuronide Injections Ameliorate Structural Osteoarthritis Changes in Rats with Destabilized Medial Meniscus

Abstract: Background: Curcumin has anti-inflammatory effects. However, curcumin is poorly water-soluble, and when administered orally, formscurcumin conjugates with poor efficacy.Curcumin monoglucuronide (TBP1901) is highly water-soluble and can existinthe free-form in a greater proportion than curcumin in vivo. This study aimed to evaluate the effectiveness of intra-articular TBP1901 injections fora rat model of osteoarthritis (OA).Methods: Sixty-four male Wistar rats (12weeks old) that had receivedthe destabilized med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 69 publications
0
0
0
Order By: Relevance
“…An additional histologic grading system (OARSI) was used to evaluate curcumin-treated OA disease. 19,21,30,40 Scores were also lower for test groups as compared to controls along with reduced synovitis and subchondral plate thickening. It was concluded that these findings provide evidence that curcumin significantly slows OA disease progression and exerts a palliative effect in an OA mouse model.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…An additional histologic grading system (OARSI) was used to evaluate curcumin-treated OA disease. 19,21,30,40 Scores were also lower for test groups as compared to controls along with reduced synovitis and subchondral plate thickening. It was concluded that these findings provide evidence that curcumin significantly slows OA disease progression and exerts a palliative effect in an OA mouse model.…”
Section: Discussionmentioning
confidence: 86%
“…Liu (2016) 29 Inflammatory cytokines and oxidative stress markers in the inhibition of OA in mice by curcumin; 4 groups (n=5/group), curcumin low dose or curcumin high dose vs positive/negative controls -1.96 Nakahata (2020) 30 Periodic curcumin monoglucuronide injections ameliorate structural DMM-induced OA changes in rats; 8 groups (n=8/group), IA inject curcumin analyzed at 4 time-points vs saline control inject same 4 timepoints -2.33 Niazvand (2017) 31 Curcumin-loaded poly lactic-co-glycolic acid nanoparticles effects on MIA-induced OA in rats; 4 groups (n=10/group), oral curcumin or nano-curcumin to treat OA vs positive/negative controls -2.58 Nicoliche (2020) 32 Evaluation of the articular cartilage in rats with IA zymosan injection induced arthritis treated with curcumin in rats; 3 groups (n=5/group), oral curcumin vs positive/negative controls -2.86 Nixon (2017) 33 Evaluation of TRB-n0224, a chemically modified curcumin for the treatment of surgical ACL transection induced OA in rabbits; 4 groups (n=10/group), oral curcumin low dose, or curcumin high dose vs positive/ negative controls -0.01 Park (2020) 34 Highly bioavailable curcumin powder suppresses articular cartilage damage in rats with MIA-induced OA in rats; 6 groups (n=13/ group, oral saline n=12), oral Theracurmin  low dose, mid-dose or high dose vs. oral saline control (no OA induced), MIA-induced OA control, NSAID treated OA control -2.58 Park (2016) 35 Curcumin and tetrahydrocurcumin both prevent OA symptoms and decrease the expressions of pro-inflammatory cytokines in estrogen-deficient rats (MIA-induced OA, ovariectomized); 5 groups (n=10/group), oral curcumin or tetrahydrocurcumin vs. normal control, positive control, or placebo control -1.96 Sun (2010) 36 Effects of curcumin on expressions of CL-2, Mmp9, Cox-2, IKKβ, NF-Кb and tissue changes in rabbit stifle cartilage OA (papain injection); 3 groups (n=10/group), IA inject curcumin for OA group, saline IA for OA versus untreated control -1.96 Sun (2017) 37 Curcumin prevents DMM-induced OA in mice by inhibiting the activation of inflammasome NLRP3; 5 groups (n=8/group), IP inject curcumin for OA, DMSO for OA versus no surgery control. sham control, OA with no treatment -2.58 38 Involvement of TLR4 in the protective effect of administration of curcumin on rat surgical ACL transection induced OA; 5 groups (n=10/group); IA curcumin, IA curcumin + lipopolysacchaide (LPS) inject vs positive/negative controls, LPS inject only -1.96 Zhang (2019) 39 Curcumin reduces inflammation in MIA-induced OA in rats through blocking TLR4/MyD88/NK-κB signal pathway; 4 groups (n=12/group); curcumin, curcumin + PBS vs positive/negative controls -1.96…”
Section: Resultsmentioning
confidence: 99%